Estudio de la práctica de valores en los adolescentes de 15 a 17 años de la parroquia el Sagrario del cantón Loja y la intervención del trabajador social, en el período abril-agosto del 2015. - Pezantes Sigcho, Martha Irene (2016)
Part of the social and human coexistence requires daily practice and application of values, with the aim of strengthening long-term relationships, causing increased both personal, family or social welfare, depending on the level of interpersonal relations that each person established in the community to which it belongs, however, it is necessary to control and promote the new generations represented by adolescents practice of values, so the following problem: There will be young people between the ages of 15 to 17 years that even established practice of values? In order to corroborate or dismiss the problem under study establishes the general objective of " improving the quality of life of young people 15 to 17 years old by practicing human values in the parish El Sagrario Canton Loja"; likewise, its development has been supported by the application of the following research methods are scientific, inductive, deductive method; statistical and bibliographic; the application of techniques such as the survey of teenagers in the parish of Canton Loja El Sagrario, between the ages of 15 to 17 years still evident; plus an interview addressed to Social Workers Autonomous Municipal Government of Loja and Amparo Municipal Board of Loja. Using the results obtained in the adolescent population of the parish El Sagrario, it was found that there is an adequate level of behavior inside and outside the home, like relations with neighbors in the practice of values is regular, by several factors that they have influenced the behavioral levels of new generations of young people, whose habits are far from the use of securities as regulatory constraints of interpersonal relationships, which is corroborated by interviews which details the same problems and even relate to behavior problems that can lead to social problems, it is concluded that students maintain a variation in levels of behavior either within your home, how out of it, recommending teens who make a personal commitment to sustain the same behavior both within the home and outside it, leaving aside false prejudices, to regulate their conduct with the lack of control by the absence of their parents. In this paper the study of the actions of a professional social work is elementary, because when it became apparent the need for intervention, or professional in question is clear, adequate knowledge to be undertaken to address the problem and based an intervention plan to help improve the qualities of behavior subject to the application of values, the same that are assimilated into the needs of adolescents and analyzing their behavior.